2007
DOI: 10.1117/12.720848
|View full text |Cite
|
Sign up to set email alerts
|

Statistically and perceptually motivated nonlinear image representation

Abstract: We describe an invertible nonlinear image transformation that is well-matched to the statistical properties of photographic images, as well as the perceptual sensitivity of the human visual system. Images are first decomposed using a multi-scale oriented linear transformation. In this domain, we develop a Markov random field model based on the dependencies within local clusters of transform coefficients associated with basis functions at nearby positions, orientations and scales. In this model, division of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Although RG is unlikely to remain optimal in the presence of channel noise, we expect that a globally extended RG transform might still be effective for image compression. In previous work, we found that divisively normalized representations can produce improvements in the rate-distortion trade-off (for MSE and in terms of visual quality) compared with their linear counterparts (Lyu & Simoncelli, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although RG is unlikely to remain optimal in the presence of channel noise, we expect that a globally extended RG transform might still be effective for image compression. In previous work, we found that divisively normalized representations can produce improvements in the rate-distortion trade-off (for MSE and in terms of visual quality) compared with their linear counterparts (Lyu & Simoncelli, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Empirically, it has been shown that locally dividing bandpass-filtered pixels by local standard deviation can produce approximately gaussian marginal distributions (Ruderman, 1996) and that a weighted DN nonlinearity can reduce statistical dependencies of oriented bandpass filter responses (Simoncelli, 1997;Buccigrossi & Simoncelli, 1999;Schwartz & Simoncelli, 2001;Valerio & Navarro, 2003). Recently, several authors have developed invertible image transformations that incorporate DN (Malo et al, 2000;Malo, Epifanio, Navarro, & Simoncelli, 2006;Gluckman, 2006;Lyu & Simoncelli, 2007). Since DN provides a nonlinear means of reducing dependencies in bandpass representations of images, it is natural to ask how it is related to the RG methodology introduced in this article.…”
Section: Relationship To Divisive Normalizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The DNT is built upon linear transform models, where each coefficient (or neuronal response) is normalized (divided) by the energy of a cluster of neighboring coefficients (neighboring neuronal response) [14]. This procedure can explain nonlinearities in the responses of mammalian cortical neurons, and nonlinear masking phenoma in human visual perception, and was also empirically shown to produce approximately Gaussian marginal distributions and to reduce the statistical dependencies of the original linear representation [19]. Therefore, we proposed a change detection method for SAR images in the DNT domain rather than in the wavelet domain due to the superior properties of the DNT as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…This normalization is conceptually consistent with the light adaptation (also called luminance masking) and contrast masking effect of HVS. It has been recognized as an efficient perceptually and statistically non-linear image representation model [32,33]. It is shown to be a useful framework that accounts for the masking effect in human visual system, which refers to the reduction of the visibility of an image component in the presence of large neighboring components [34,35].…”
Section: Ssim-optimal Local Model From Sparse Representationmentioning
confidence: 99%